Media and the Management of Electoral Violence: A Study of General Elections in Bauchi State, Nigeria 2007-2011 - SALEH, Musa; YAHAYA, Yusuf Musa; MUKHTAR, Sagir (Socialscientia: Journal of Social Sciences and Humanities, 2023)
Electoral violence is one of the major challenges affecting peaceful coexistence across the globe. Bauchi State is not an exception because the prevalence of electoral violence within the state has caused a public outcry. This study investigated media and the management of electoral violence: A study of General Elections in Bauchi State, Nigeria 2007 to 2011. A quantitative research design was adopted. The research instrument used for data collection in this study was a questionnaire designed. The internal consistency of the reliability test was 0.72 and it is acceptable. The data collected was computed using percentages and frequency distribution tables. The hypotheses were subjected to inferential statistics while Chi-square was tested at α 0.05 level of significance. The study findings reveal the majority of the respondents agreed that poor remuneration, poor journalism, ethnicity, and religious and political affiliation are factors responsible for electoral violence within the study area. The study findings also confirmed that media organizations played a vital role in terms of media sensitization, the autonomy of the media houses, media regulation, and professionalism of the media houses addressed the electoral violence in the Bauchi metropolis. The study concludes that poor remuneration of the journalists allowed them to collect brown envelop and cause conflict during the election, and poor journalism allowed the media houses to spread biased information across the communities. The study recommends that the remuneration package of the journalist should be increased from time to time, and regular media sensitization should be encouraged in order to avoid hate speech.